Preparation method of sulfur-tolerant reversed-phase combustion catalyst, prepared catalyst and application of sulfur-tolerant reversed-phase combustion catalyst

By using reverse phase structure and sulfur-resistant active components in low-carbon alkane combustion catalyst, the problem of catalyst inactivation and poisoning in sulfur environment is solved, and efficient and stable catalytic performance and long life are achieved.

CN119869520APending Publication Date: 2025-04-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411850022.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing low-carbon alkane combustion catalysts show poor sulfur resistance and stability in sulfur environments, resulting in catalyst deactivation and poisoning.

Method used

A sulfur-resistant reverse phase combustion catalyst with an inverted phase structure is used. By adding surfactant and sulfur-resistant active component precursors on the basis of metal oxides and binders, it is impregnated and hot air drying, and finally soaked in NaBH4 solution to improve the stability of the catalyst.

Benefits of technology

Under high airspeed conditions, the catalyst exhibits high catalytic activity and stability, has good sulfur resistance, long service life, simple preparation process and low manufacturing cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869520A_ABST
    Figure CN119869520A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sulfur-tolerant reversed-phase combustion catalyst, the catalyst prepared by the preparation method and application of the sulfur-tolerant reversed-phase combustion catalyst. Comprising the following steps: (1) mixing a metal oxide, a binder, a surfactant and water, regulating the pH value to 2-10 by using a pH value regulator, and carrying out ball milling to obtain coating slurry; (2) impregnating a carrier I in the coating slurry, drying, repeatedly impregnating I and drying with hot air for multiple times, and roasting to obtain a carrier loaded with a metal oxide; (3) dipping the carrier loaded with the metal oxide in a solution of a solvent I containing an active metal precursor and an oxide precursor, drying and roasting to obtain a catalyst precursor; and (4) dipping the catalyst precursor III in a solvent II solution containing a sulfur-tolerant active component precursor, drying, roasting, soaking in a 0.01-1mol / L NaBH4 aqueous solution for 0.1-24 hours, soaking for 1-10 times, and drying to obtain the sulfur-tolerant reversed-phase combustion catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing a sulfur-resistant reverse combustion catalyst, a catalyst prepared therefrom and applications thereof, and belongs to the field of chemistry and chemical engineering. Background Art

[0002] With the rapid development of modern industry, volatile organic compounds (VOCs) have become one of the main components of air pollutants and have caused serious harm to the ecological environment and human health. Therefore, how to effectively control and eliminate VOCs has become one of the research hotspots in the field of environmental protection. Among the many technologies for VOCs emission control, catalytic combustion is considered to be the most effective method. Among them, alkane volatile organic compounds are considered to be the most stable and most difficult to eliminate components in VOCs, and are produced in large quantities in petrochemical industries such as refineries and oil fields and automobile exhaust emissions. These pollutants can cause great harm to human health and also cause a serious greenhouse effect. Therefore, it is necessary to develop high-performance and high-stability catalysts to effectively reduce and eliminate the emission of low-carbon alkanes.

[0003] For the treatment of sulfur-containing industrial tail gas, sulfur poisoning of the catalyst is an important factor affecting the life of the catalyst. For volatile organic combustion catalysts containing hydrogen sulfide, the active sites are easily corroded by sulfur during the catalytic reaction, causing the catalyst to be deactivated. Hydrogen sulfide not only competes with VOCs molecules for adsorption active sites, but also reacts with catalyst components to oxidize and generate sulfates that cover the catalyst surface, destroying the catalyst structure, reducing active sites, causing catalyst poisoning, and inhibiting catalytic activity. Therefore, catalytic combustion technology faces the application difficulty of designing and developing hydrogen sulfide-resistant catalysts.

[0004] CN105709854A discloses a metal-based catalytic combustion catalyst and a preparation method thereof. The metal-based catalyst cannot operate stably for a long time under high water vapor and high SO2 conditions. Chinese patent CN102553585A discloses a sulfur-resistant catalyst for gas deoxidation and its preparation method and application. Mo is added to the catalyst, and presulfurization is required to ensure the sulfur resistance of the catalyst, but the activity of the catalyst is not high. Chinese patent CN89105594.0 discloses a "sulfur-containing organic waste gas incineration catalyst and preparation method thereof". The catalyst uses natural mordenite treated with sulfuric acid as a carrier, V2O5 as an active component, and precious metals such as platinum and palladium as auxiliary. The catalyst has a good effect on the oxidation of sulfur-containing organic matter, and also has a good purification effect on CO, low-carbon alkanes, and oxygen-containing organic matter. Summary of the invention

[0005] In view of the poor sulfur resistance and stability of currently disclosed low-carbon alkane combustion catalysts, the present invention proposes a sulfur-resistant reverse combustion catalyst and a preparation method thereof.

[0006] The "metal-oxide" interface plays a vital role in catalytic applications: on the one hand, the oxide adjusts the d-charge of the metal particles through electronic interaction (EMSI) with the metal, thereby achieving the purpose of regulating catalytic activity and selectivity; on the other hand, the metal site and the oxide site (non-inert) serve as activation sites for different substrate molecules respectively, and their synergistic catalysis can often show unique performance beyond a single site. Compared with traditional oxide catalysts, the oxide nanoparticles in the reverse catalyst system are in a highly dispersed state, which is more suitable for exploring the catalytic effect of oxide sites. The advantages of reverse catalysts are mainly reflected in three aspects: (1) providing interfacial active sites for interfacial catalysis and catalytic reaction mechanism research; (2) providing highly dispersed oxide sites for oxide nanoparticle property and function research; (3) providing sintering-resistant oxides and large-sized metals to improve the stability of the catalyst. The catalyst provided by the present invention has a reverse structure.

[0007] According to one aspect of the present application, a method for preparing a sulfur-resistant reverse combustion catalyst is provided, comprising the following steps:

[0008] (1) mixing a metal oxide, a binder, a surfactant and water, adjusting the pH value to 2 to 10 with a pH adjuster, and ball milling to obtain a coating slurry;

[0009] (2) dipping the carrier into the coating slurry, blowing out the excess slurry liquid in the honeycomb carrier pores with compressed air, drying with hot air, repeating the dipping and hot air drying for multiple times, and calcining to obtain a carrier loaded with metal oxides;

[0010] (3) impregnating the carrier loaded with metal oxide II into a solvent I solution containing an active metal precursor and an oxide precursor, blowing out the excess solution in the pores of the honeycomb carrier with compressed air, drying with hot air, and calcining to obtain a catalyst precursor;

[0011] (4) Impregnating the catalyst precursor III in a solvent II solution containing a sulfur-resistant active component precursor, blowing out excess solution in the honeycomb carrier pores with compressed air, drying with hot air, calcining, soaking in a 0.01-1 mol / L NaBH4 aqueous solution for 0.1-24 h, soaking 1-10 times, blowing out excess solution in the honeycomb carrier pores with compressed air, drying with hot air, and obtaining the sulfur-resistant reverse combustion catalyst.

[0012] The metal oxide is selected from at least one of aluminum oxide, titanium oxide, cerium oxide, zirconium oxide, yttrium oxide, neodymium oxide, tin oxide, and chromium oxide;

[0013] The binder is selected from at least one of silica sol, aluminum sol, titanium sol and zirconium sol;

[0014] The surfactant is selected from at least one of polyethylene glycol, glycerol, carboxymethyl cellulose, polyvinyl alcohol and polypropylene alcohol;

[0015] The pH regulator is selected from at least one of formic acid, acetic acid, hydrochloric acid, citric acid, phosphoric acid, nitric acid, ammonia water, sodium carbonate and sodium hydroxide;

[0016] The mass ratio of the metal oxide, the binder and the surfactant is 10-500:1-30:0.05-3;

[0017] The solid content of the coating slurry is 5 to 50 wt %;

[0018] The rotation speed of the ball mill is 200-500 rpm;

[0019] The ball milling time is 1 to 20 hours.

[0020] The carrier is a honeycomb carrier;

[0021] The time of the immersion I is 5 to 60 seconds.

[0022] The active metal precursor is selected from at least one of palladium nitrate, chloroplatinic acid, osmium chloride, chloroiridic acid, ruthenium chloride, and rhodium chloride;

[0023] The oxide precursor is selected from at least one of cobalt nitrate, chromium nitrate, iron nitrate, ammonium molybdate, ammonium metavanadate, nickel nitrate, ammonium paratungstate, copper nitrate, and zinc nitrate;

[0024] The solvent I is selected from at least one of water, ethanol and methanol;

[0025] In the solvent I solution containing the active metal precursor and the oxide precursor, the concentration of the active metal precursor is 0.2-10 wt %, and the concentration of the oxide precursor is 0.2-40 wt %;

[0026] The time of the immersion II is 10 to 1800 seconds.

[0027] The sulfur-resistant active component precursor is selected from at least one of ferric nitrate, copper nitrate, lanthanum nitrate, tin chloride, nickel nitrate, zinc nitrate, praseodymium nitrate, chromium nitrate, manganese nitrate, cerium nitrate, yttrium nitrate, ammonium molybdate, ammonium metavanadate, and neodymium nitrate;

[0028] The solvent II is selected from at least one of water, ethanol and methanol;

[0029] In the solvent II solution containing the sulfur-resistant active component precursor, the concentration of the sulfur-resistant active component precursor is 0.2 to 40 wt %;

[0030] The time of the impregnation III is 10 to 1800 seconds.

[0031] The temperature of the hot air drying is 100-160°C;

[0032] The hot air drying time is 1 to 15 minutes;

[0033] The gas flow rate of the hot air drying is 0.2 to 2 m / s;

[0034] The calcination temperature is 400-900°C;

[0035] The calcination time is 1 to 10 hours.

[0036] According to another aspect of the present application, a sulfur-resistant reverse combustion catalyst prepared by the above-mentioned preparation method is provided.

[0037] According to another aspect of the present application, a method for efficiently removing and purifying sulfur-containing low-carbon alkane gas is provided, using the above-mentioned sulfur-resistant reverse combustion catalyst.

[0038] The beneficial effects of this application include:

[0039] 1. The sulfur-resistant reverse combustion catalyst of the present invention has high catalytic activity and stability under high space velocity conditions;

[0040] 2. The sulfur-resistant reverse combustion catalyst of the present invention has a simple preparation process and low manufacturing cost;

[0041] 3. The sulfur-resistant reverse combustion catalyst of the present invention has good sulfur resistance, small catalyst resistance drop and long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 : Reaction conditions - stability evaluation of working example 1.

[0043] Figure 2 : Stability evaluation of reaction condition 2 working condition Example 1. DETAILED DESCRIPTION

[0044] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0045] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0046] Embodiment 1:

[0047] Weigh 30g of titanium dioxide, 12g of silica sol, 1ml of concentrated ammonia water, and 0.25g of polyethylene glycol and add them to 70g of deionized water with a pH value of 8-9. Add the mixture into a ball mill and mill it at a speed of 500 rpm for 2 hours to obtain a coating slurry. Immerse a 15*15*20mm 200-mesh honeycomb ceramic carrier in the coating slurry for 20s, and blow out excess slurry liquid in the pores of the honeycomb carrier with compressed air; then dry it with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, repeat the above process until the coating mass accounts for 20% to 22% of the mass of the entire honeycomb carrier before coating, and calcine at 500°C for 4 hours to obtain a honeycomb carrier loaded with C. 100g of a mixed aqueous solution with a palladium nitrate concentration of 0.6% and a chromium nitrate concentration of 17.5% was prepared as an impregnation solution A, and the honeycomb carrier loaded with C was immersed in the impregnation solution A for 60s, and the excess impregnation liquid in the pores of the honeycomb carrier was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN. 100g of an aqueous solution with a chromium nitrate concentration of 0.2% was prepared as an impregnation solution B, and the honeycomb carrier loaded with MN was immersed in the impregnation solution B for 60s, and the excess impregnation liquid in the pores of the honeycomb carrier was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN / L. The prepared honeycomb carrier loaded with MN / L was immersed in a 0.1 mol / L NaBH4 aqueous solution for 3 h, washed and immersed for 6 times, and then the excess solution in the pores of the honeycomb carrier was blown out with compressed air; after hot air drying for 10 min, a reduced integral structure catalyst was obtained.

[0048] Embodiment 2:

[0049] Weigh 30g of zirconium dioxide, 12g of zirconium sol, 0.5ml of concentrated nitric acid, and 0.2g of polyvinyl alcohol and add them into 70g of deionized water with a pH value of 3-4. Add the mixture into a ball mill and mill it at a speed of 500 rpm for 2 hours to obtain a coating slurry. Immerse a 15*15*20mm 200-mesh honeycomb ceramic carrier in the coating slurry for 20s, and blow out excess slurry liquid in the pores of the honeycomb carrier with compressed air; then dry it with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, repeat the above process until the coating mass accounts for 20%-22% of the mass of the entire honeycomb carrier before coating, and calcine at 500°C for 4 hours to obtain a honeycomb carrier loaded with C. 100g of a mixed aqueous solution with a palladium nitrate concentration of 0.6% and a chromium nitrate concentration of 17.5% was prepared as an impregnation solution A, and the honeycomb carrier loaded with C was immersed in the impregnation solution A for 60s, and the excess impregnation liquid in the pores of the honeycomb carrier was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN. 100g of an aqueous solution with a cerium nitrate concentration of 0.2% was prepared as an impregnation solution B, and the honeycomb carrier loaded with MN was immersed in the impregnation solution B for 60s, and the excess impregnation liquid in the pores of the honeycomb carrier was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN / L. The prepared honeycomb carrier loaded with MN / L was immersed in a 0.1 mol / L NaBH4 aqueous solution for 3 h, washed and immersed for 6 times, and then the excess solution in the pores of the honeycomb carrier was blown out with compressed air; after hot air drying for 10 min, a reduced integral structure catalyst was obtained.

[0050] Embodiment 3:

[0051] Weigh 30g of aluminum oxide, 12g of aluminum sol, 0.75ml of concentrated nitric acid, and 0.25g of polyvinyl alcohol and add them into 70g of deionized water with a pH value of 3-4. Add the mixture into a ball mill and mill it at a speed of 500 rpm for 2 hours to obtain a coating slurry. Immerse a 15*15*20mm 200-mesh honeycomb ceramic carrier in the coating slurry for 20s, and blow out excess slurry liquid in the pores of the honeycomb carrier with compressed air; then dry it with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, repeat the above process until the coating mass accounts for 20%-22% of the mass of the entire honeycomb carrier before coating, and calcine at 500°C for 4 hours to obtain a honeycomb carrier loaded with M1. 100g of a mixed aqueous solution with a palladium nitrate concentration of 0.6% and a chromium nitrate concentration of 17.5% was prepared as an impregnation solution A, and the honeycomb carrier loaded with C was immersed in the impregnation solution A for 60s, and the excess impregnation liquid in the pores of the honeycomb carrier was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN. 100g of an aqueous solution with a concentration of 0.2% ammonium metavanadate was prepared as an impregnation solution B, and the honeycomb carrier loaded with MN was immersed in the impregnation solution B for 60s, and the excess impregnation liquid in the pores of the honeycomb carrier was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN / L. The prepared honeycomb carrier loaded with MN / L was immersed in a 0.1 mol / L NaBH4 aqueous solution for 3 h, washed and immersed for 6 times, and then the excess solution in the pores of the honeycomb carrier was blown out with compressed air; after hot air drying for 10 min, a reduced integral structure catalyst was obtained.

[0052] Embodiment 4:

[0053] Weigh 30g of titanium dioxide, 12g of silica sol, 1ml of concentrated ammonia water, and 0.25g of polyethylene glycol and add them to 70g of deionized water with a pH value of 8-9. Add the mixture into a ball mill and mill it at a speed of 500 rpm for 2 hours to obtain a coating slurry. Immerse a 15*15*20mm 200-mesh honeycomb ceramic carrier in the coating slurry for 20s, and blow out excess slurry liquid in the pores of the honeycomb carrier with compressed air; then dry it with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, repeat the above process until the coating mass accounts for 20% to 22% of the mass of the entire honeycomb carrier before coating, and calcine at 500°C for 4 hours to obtain a honeycomb carrier loaded with C. 100g of a mixed aqueous solution with a palladium nitrate concentration of 0.6% and a cobalt nitrate concentration of 24.16% in Heshui was prepared as an impregnation solution A, and the honeycomb carrier loaded with C was immersed in the impregnation solution A for 60s, and the excess impregnation liquid in the holes of the honeycomb carrier was blown out with compressed air; then it was dried with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN. 100g of an aqueous solution with a ferric nitrate concentration of 16.8% in Heshui was prepared as an impregnation solution B, and the honeycomb carrier loaded with MN was immersed in the impregnation solution B for 60s, and the excess impregnation liquid in the holes of the honeycomb carrier was blown out with compressed air; then it was dried with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN / L. The prepared honeycomb carrier loaded with MN / L was immersed in a 0.1 mol / L NaBH4 aqueous solution for 3 h, washed and immersed for 6 times, and then the excess solution in the pores of the honeycomb carrier was blown out with compressed air; after hot air drying for 10 min, a reduced integral structure catalyst was obtained.

[0054] Embodiment 5:

[0055] Weigh 30g of titanium dioxide, 12g of silica sol, 1ml of concentrated ammonia water, and 0.25g of polyethylene glycol and add them to 70g of deionized water with a pH value of 8-9. Add the mixture into a ball mill and mill it at a speed of 500 rpm for 2 hours to obtain a coating slurry. Immerse a 15*15*20mm 200-mesh honeycomb ceramic carrier in the coating slurry for 20s, and blow out excess slurry liquid in the pores of the honeycomb carrier with compressed air; then dry it with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, repeat the above process until the coating mass accounts for 20% to 22% of the mass of the entire honeycomb carrier before coating, and calcine at 500°C for 4 hours to obtain a honeycomb carrier loaded with C. 100g of a mixed aqueous solution with a palladium nitrate concentration of 0.6% and a triple-water copper nitrate concentration of 20.08% was prepared as an impregnation solution A, and the honeycomb carrier loaded with C was immersed in the impregnation solution A for 60s, and the excess impregnation liquid in the pores of the honeycomb carrier was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN. 100g of an aqueous solution with a concentration of ammonium molybdate of 4.09% was prepared as an impregnation solution B, and the honeycomb carrier loaded with MN was immersed in the impregnation solution B for 60s, and the excess impregnation liquid in the pores of the honeycomb carrier was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN / L. The prepared honeycomb carrier loaded with MN / L was immersed in a 0.1 mol / L NaBH4 aqueous solution for 3 h, washed and immersed for 6 times, and then the excess solution in the pores of the honeycomb carrier was blown out with compressed air; after hot air drying for 10 min, a reduced integral structure catalyst was obtained.

[0056] Embodiment 6:

[0057] Weigh 30g of titanium dioxide, 12g of silica sol, 1ml of concentrated ammonia water, and 0.25g of polyethylene glycol and add them to 70g of deionized water with a pH value of 8-9. Add the mixture into a ball mill and mill it at a speed of 500 rpm for 2 hours to obtain a coating slurry. Immerse a 15*15*20mm 200-mesh honeycomb ceramic carrier in the coating slurry for 20s, and blow out excess slurry liquid in the pores of the honeycomb carrier with compressed air; then dry it with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, repeat the above process until the coating mass accounts for 20% to 22% of the mass of the entire honeycomb carrier before coating, and calcine at 500°C for 4 hours to obtain a honeycomb carrier loaded with C. 100g of a mixed aqueous solution with a palladium nitrate concentration of 0.6% and a nickel nitrate concentration of 25.95% in hexahydrate water was prepared as an impregnation solution A, and the honeycomb carrier loaded with C was immersed in the impregnation solution A for 60s, and the excess impregnation liquid in the honeycomb carrier pores was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN. 100g of an aqueous solution with a tin tetrachloride concentration of 7.78% in hexahydrate water was prepared as an impregnation solution B, and the honeycomb carrier loaded with MN was immersed in the impregnation solution B for 60s, and the excess impregnation liquid in the honeycomb carrier pores was blown out with compressed air; then it was dried by hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, and baked at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component material MN / L. The prepared honeycomb carrier loaded with MN / L was immersed in a 0.1 mol / L NaBH4 aqueous solution for 3 h, washed and immersed for 6 times, and then the excess solution in the pores of the honeycomb carrier was blown out with compressed air; after hot air drying for 10 min, a reduced integral structure catalyst was obtained.

[0058] Comparative Example:

[0059] Weigh 30g of titanium dioxide, 12g of silica sol, 1ml of concentrated ammonia water, and 0.25g of polyethylene glycol and add them to 70g of deionized water with a pH value of 8-9. Add the mixture into a ball mill and mill it at a speed of 500 rpm for 2 hours to obtain a coating slurry. Immerse a 15*15*20mm 200-mesh honeycomb ceramic carrier in the coating slurry for 20s, and blow out excess slurry liquid in the pores of the honeycomb carrier with compressed air; then dry it with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100s, repeat the above process until the coating mass accounts for 20% to 22% of the mass of the entire honeycomb carrier before coating, and calcine at 500°C for 4 hours to obtain a honeycomb carrier loaded with C. Prepare 100g of aqueous solution with a concentration of 0.6% palladium nitrate as impregnation solution A, immerse the honeycomb carrier loaded with C in the impregnation solution A for 60 seconds, blow out the excess impregnation solution in the pores of the honeycomb carrier with compressed air; then dry it with hot air (temperature 120°C, pore gas flow rate 0.8m / s) for 100 seconds, and bake it at 500°C for 4 hours to obtain a honeycomb carrier loaded with active component materials. Soak the prepared honeycomb carrier loaded with active component materials in a 0.1mol / L NaBH4 aqueous solution for 3 hours, wash and soak it 6 times, then blow out the excess solution in the pores of the honeycomb carrier with compressed air; after hot air drying for 10 minutes, obtain a reduced integral structure catalyst.

[0060] The activity and stability of the sulfur-containing low-carbon alkane gas purification catalysts of Examples 1-6 and the comparative example were evaluated. Reaction conditions 1: C2H6 = 0.1%, C3H8 = 0.1%, Air, H2S = 10ppm, reaction temperature: 400°C, reaction space velocity 10000h -1 Attached Figure 2 Reaction conditions 2: Toluene = 0.05%, Air, SO2 = 0.003%, reaction temperature 212-222°C, reaction space velocity 150000h -1 .

[0061] The catalyst activity and stability are shown in the following table (reaction conditions: C2H6 = 0.1%, C3H8 = 0.1%, Air, H2S = 10ppm, reaction space velocity 10000h -1 ).

[0062]

[0063] It can be seen from the table that under reaction condition 1, the catalytic oxidation activity and stability of light alkanes of the catalysts obtained in Examples 1-6 are significantly better than those of the catalysts obtained in the comparative examples.

[0064] Figure 1: Stability evaluation of the catalyst obtained in Example 1. It can be seen from the figure that the catalyst of Example 1 has good catalytic oxidation activity of light alkanes under H2S-containing conditions.

[0065] Figure 2 : Stability evaluation of the catalyst obtained in Example 1. It can be seen from the figure that the catalyst in Example 1 has good catalytic oxidation activity for toluene under SO2 conditions.

[0066] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a sulfur-resistant reverse combustion catalyst, characterized in that: The following steps are involved: (1) mixing a metal oxide, a binder, a surfactant and water, adjusting the pH value to 2 to 10 with a pH adjuster, and ball milling to obtain a coating slurry; (2) impregnating the support I in the coating slurry, drying with hot air, repeating the impregnation I and hot air drying multiple times, and calcining to obtain a support loaded with metal oxide; (3) impregnating the support loaded with metal oxide II into a solvent I solution containing an active metal precursor and an oxide precursor, drying with hot air, and calcining to obtain a catalyst precursor; (4) Impregnating the catalyst precursor III in a solvent II solution containing a sulfur-resistant active component precursor, drying with hot air, calcining, soaking in a 0.01-1 mol / L NaBH4 aqueous solution for 0.1-24 h, soaking 1-10 times, and drying with hot air to obtain the sulfur-resistant reverse combustion catalyst.

2. The preparation method according to claim 1, characterized in that: The metal oxide is selected from at least one of aluminum oxide, titanium oxide, cerium oxide, zirconium oxide, yttrium oxide, neodymium oxide, tin oxide, and chromium oxide; The binder is selected from at least one of silica sol, aluminum sol, titanium sol and zirconium sol; The surfactant is selected from at least one of polyethylene glycol, glycerol, carboxymethyl cellulose, polyvinyl alcohol and polypropylene alcohol; The pH regulator is selected from at least one of formic acid, acetic acid, hydrochloric acid, citric acid, phosphoric acid, nitric acid, ammonia water, sodium carbonate and sodium hydroxide; The mass ratio of the metal oxide, the binder and the surfactant is 10-500:1-30:0.05-3; The solid content of the coating slurry is 5 to 50 wt %; The rotation speed of the ball mill is 200-500 rpm; The ball milling time is 1 to 20 hours.

3. The preparation method according to claim 1, characterized in that: The carrier is a honeycomb carrier; The time of the immersion I is 5 to 60 seconds.

4. The preparation method according to claim 1, characterized in that: The active metal precursor is selected from at least one of palladium nitrate, chloroplatinic acid, osmium chloride, chloroiridic acid, ruthenium chloride, and rhodium chloride; The oxide precursor is selected from at least one of cobalt nitrate, chromium nitrate, iron nitrate, ammonium molybdate, ammonium metavanadate, nickel nitrate, ammonium paratungstate, copper nitrate, and zinc nitrate; The solvent I is selected from at least one of water, ethanol and methanol; In the solvent I solution containing the active metal precursor and the oxide precursor, the concentration of the active metal precursor is 0.2-10 wt %, and the concentration of the oxide precursor is 0.2-40 wt %; The time of the immersion II is 10 to 1800 seconds.

5. The preparation method according to claim 1, characterized in that: The sulfur-resistant active component precursor is selected from at least one of ferric nitrate, copper nitrate, lanthanum nitrate, tin chloride, nickel nitrate, zinc nitrate, praseodymium nitrate, chromium nitrate, manganese nitrate, cerium nitrate, yttrium nitrate, ammonium molybdate, ammonium metavanadate, and neodymium nitrate; The solvent II is selected from at least one of water, ethanol and methanol; In the solvent II solution containing the sulfur-resistant active component precursor, the concentration of the sulfur-resistant active component precursor is 0.2 to 40 wt %; The time of the impregnation III is 10 to 1800 seconds.

6. The preparation method according to claim 1, characterized in that: The temperature of the hot air drying is 100-160°C; The hot air drying time is 1 to 15 minutes; The gas flow rate of the hot air drying is 0.2 to 2 m / s; The calcination temperature is 400-900°C; The calcination time is 1 to 10 hours.

7. A sulfur-resistant reverse combustion catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. A method for efficiently removing and purifying sulfur-containing low-carbon alkane gas, characterized in that: The sulfur-resistant reverse combustion catalyst according to claim 7 is used.

Citation Information

Patent Citations

  • Sulfur-tolerant catalyst for gas deoxidation as well as preparation method and application thereof

    CN102553585A

  • Containing-sulphur organic catalyst to burned waste gas and its preparation

    CN1049299A

  • Metal-matrix catalytic combustion catalyst and preparation method thereof

    CN105709854A